PERANCANGAN ARSITEKTUR SISTEM INFORMASI MENGGUNAKAN ENTERPRISE ARSITECTURE PLANNING (Studi Kasus: Badan Pendidikan dan Pelatihan Daerah Kab. Lampung Tengah) - kurniawan, hendra (IIB Darmajaya, 2013)
One form of improved services and performance of the functions of an agency is a well-defined business and data processing activities that follow the development of information and communication technology, So that it can realize its strategic objectives. One way that can be taken is to conduct agency enterprise architecture definition. In this study, a case study on Badan Pendidikan dan Pelatihan Daerah Kabupaten Lampung Tengah using the enterprise architecture planning (EAP) and generates blueprints information systems. In this study, the steps undertaken by the EAP, such as initiation planning, business modeling, systems and current technology, data architecture, application architecture, technology architecture, and the last is the implementation plan. After doing the whole process of the EAP, then the resulting 36 data entities and 28 candidate applications in 8 activities and training functions of the Board of Education Central Lampung District. With the resulting 36 entities and 28 candidate applications on the agency to contribute in the development of information systems in the future. Due to the blueprint of information system resulting from this study as a benchmark in the development of information systems. Keywords: Enterprise Architecture Planning, Arsitektur Enterprise